Plantas medicinais e saúde bucal: estudo etnobotânico, atividade antimicrobiana e potencial para interação medicamentosa. - Cavalcante, Ana Lúcia Furtado de Almeida (2010)
The aim of this work was to identify through an Etnobotanic study the most used medicinal plants for health treatment of oral diseases and to evaluate the antibacterial activity and the potential for medicine interactions (antibiotics) during the use of medicinal plants. For this purpose the study was performed in the municipal districts of Cruz do Espírito Santo, Guarabira, Jacaraú, João Pessoa, Mamanguape, Santa Rita and Sapé, where 62 healers, 385 users and 197 dentists participated in an interview. They answered to subjects that involved socioeconomic and cultural variables and other factors relative to the use of medicinal plants for oral health. The antimicrobial activity of the most cited plants (n=5) was evaluated. To evaluate the antibacterial activity of the crude ethanolic extracts and decocts of the peels of Abarema cochliacarpos (Gomes) Barneby & J.W. Grimes (barbatimão), Anacardium occidentale L., (cashew tree-purple), Punica granatum L. (pomegranate), Schinus terebinthifolius Raddi (aroeira) and Ziziphus joazeiro Mart. (juá) were tested against strains of Streptococcus mutans (ATCC25175), Streptococcus mutans (ATCC700610), Streptococcus oralis (ATCC10557), Streptococcus salivarius (ATCC7073) and Staphylococcus aureus (ATCC6538), the Minimal Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (CBM) were determined for all strains through the diffusion method in solid medium, using disks of filter paper and using the microdilution method in broth, using plates of 96 wells. The interference of the crude extracts and decocts of the peels of the plants in the activity of the antibiotics Ampicillin 10μg/mL, Amoxicillin 10μg/mL and Cefalexina 30μg/mL was evaluated in an experimental model of microdiluição in broth. The results of the diffusion method evidenced that, except for the decoct of the Ziziphus joazeiro Mart., with activity just against Streptococcus mutans (ATCC25175) and the decot of Punica granatum L. against Streptococcus salivarius (ATCC7073), all the other tested products showed activity antimicrobial activity against all microorganisms. The diameters of halos varing from 12 to 28mm for the crude extracts and varying from 6 to18mm for the decocts. The MIC varying from 15 a 150 μg/mL and the 200 a 400 mg/mL, respectively, for the crude extracts and the decocts. The CBM for the crude extracts varying from 40 to 400 μg/mL and for the decocts was >400mg/mL. It was observed synergism and antagonism effect of the extracts in the activity of the selected antibiotics. The results of this study indicate that the medicinal plants are frequently used as therapeutic source for oral health and that there is a potential association (synergic or antagonistic) of the plants and antibiotics in this experimental model. Therefore, the most used medicinal plants evaluated presented effective biological activity (antibacterial activity). However potential associations with medicines deserves attention among users and professionals of health.